A Painted Pottery of the Second Millennium from Southern Turkey and Northern Syria - Williams, M. V. Seton
Forms — Ware — Design — Paint — Cilicia — Kültepe — The ʿAmq Plain — T. Al Judaidah — Other Syrian Sites — Catalogue.